PENGARUH PRODUKTIVITAS PENGRAJIN BATIK TERHADAP KINERJA INDUSTRI SENTRA BATIK DESA KLAMPAR PADA MASA PANDEMI - Ika Oktaviana Dewi; Dewi Pusparini (Behavioral Accounting Journal, 2021)
Productivity as a determining factor in achieving organizational goals, such as the batik industry to achieve goals must spur work productivity so that the performance of the batik industry has increased indirectly. The purpose of this study was to determine the effect of work productivity on the industrial performance of the Klampar batik center. This research includes quantitative research with associative descriptive approach. The sample selection used purposive sampling technique with sampling criteria, namely respondents who became owners and batik craftsmen, aged over 35 years and the number of batik produced in 1 month was more than 100 pieces. The questionnaire was measured using a Likert scale and tested using a data quality test, classical assumption test and hypothesis testing. The results showed that there was a significant effect between ability (X1) on industrial performance (Y) with a significance value of 0.004, there was a significant effect between work morale (X2) on industrial performance (Y) with a significance value of 0.009. While the self-development variable (X3) has no effect on industrial performance (Y) with a significance value of 0.640